2011
DOI: 10.1002/ptr.3417
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Inhibits α‐MSH‐stimulated Melanogenesis in B16F10 Melanoma Cells

Abstract: Quercetin is known to inhibit tyrosinase activity and melanin production in melanocytes. However, several reports suggest that quercetin has different and opposite effects on melanogenesis. This study examined the precise effects of quercetin on melanogenesis using cell-free assay systems and melanocytes. Quercetin inhibited the monophenolase and diphenolase activities of tyrosinase, and melanin synthesis in cell-free assay systems. Quercetin induced mild stimulation of the tyrosinase activity and dihydroxyphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 34 publications
3
35
0
Order By: Relevance
“…It was also reported that quercetin, kaempferol and flavonoids such as compounds found in Semen cuscutae extract have been known to inhibitory effect against tyrosinase activity (Kubo and Kinst-Hori, 1999;Rho et al, 2011;Yang et al, 2011b). In spite of the modern pharmacological studies of Semen cuscutae, the molecular mechanisms of the anti-melanogenic effects have not been elucidated.…”
Section: Discussionmentioning
confidence: 94%
“…It was also reported that quercetin, kaempferol and flavonoids such as compounds found in Semen cuscutae extract have been known to inhibitory effect against tyrosinase activity (Kubo and Kinst-Hori, 1999;Rho et al, 2011;Yang et al, 2011b). In spite of the modern pharmacological studies of Semen cuscutae, the molecular mechanisms of the anti-melanogenic effects have not been elucidated.…”
Section: Discussionmentioning
confidence: 94%
“…However, quercetin has been reported to elicit the opposite effect and accelerate melanogenesis in human melanoma cells [71]. Furthermore, it was reported that the direction of its melanogenesis-regulating activity depends on the concentration of quercetin used [72]. A small number of studies have shown that quercetin derivatives can control melanogenesis.…”
Section: Synthesis Of Quercetin Derivatives and The Melanogenesis Stimentioning
confidence: 99%
“…Melanogenesis is modulated by several factors, including UV irradiation, alpha‐melanocyte‐stimulating hormone ( α ‐MSH) 7, forskolin, stem cell factor (SCF) 8, wnt‐3a 9 and isobutylmethylxanthine (IBMX) 10, within intracellular melanosomes in the melanocytes 11. Stimulation of the melanocortin 1 receptor (MC1R) by α ‐MSH activates adenyl cyclase through G protein signalling, which subsequently increases cyclic adenosine monophosphate (cAMP) production.…”
Section: Introductionmentioning
confidence: 99%